Secondary research information sources and methods. - Stewart, David W.; Kamins, Michael A. (Newbury Park, Calif. ; London : SAGE, 1993)
'Secondary Research' has been revised to give the latest information on computer-based storage and retrieval systems. The second edition features expanded coverage of computer-based information, including a new chapter on CD-ROM products and updated coverage of on-line information search services.
Previous ed.: 1984.
Includes bibliographical references and index.
Specialized.
Description based on print version record.
Keywords: Social sciences -- Research; Social sciences. -- Research